Narrativas De Un Grupo De Personas Trans Femeninas, Frente A Su Proyecto De Vida En Bogotá. - Cuervo Gacharna, Alejandra; Mahecha Benavides, Maria Alejandra (Universidad Antonio Nariño, 2025)
This study explores the narratives of transgender women regarding the construction of their life projects, understanding this as a comprehensive plan that encompasses personal, family, social, and professional dimensions, highlighting the need to understand the experiences and aspirations of this community in relation to such a relevant axis as the life project.